Iridium(III)-catalyzed selective and mild C-H amidation of cyclic N-sulfonyl ketimines with organic azides - Maraswami, Manikantha (2019)
A general protocol for iridium catalyzed direct C−H amidation of cyclic N‐sulfonyl ketimines using sulfonyl, acyl and aryl azides as nitrogen source is reported herein. The reaction takes place at room temperature with acyl and aryl azides, while an elevated temperature needed with sulfonyl azides to furnish aminated sultams in excellent yields with complete chemo and regioselectivity, thus providing a robust and environmentally benign process to the synthesis of aminosultams.